Harnessing Service Quality and Satisfaction to Unlock Consumer Loyalty in Indonesian Thriving e-commerce Market - Lisnawati, Lisnawati; Widjajanta, Bambang; Juliania, Gadis Almira; Zaki, Hafizah Omar (Politeknik Negeri Bandung, 2025)
This study investigates Indonesian e-commerce consumers' quality of e-services, e-satisfaction, and digital purchasing intent among e-commerce users in Indonesia. Using a descriptive and verification research design with a quantitative approach, 200 respondents' data was acquired using purposive non-probability sampling. A consideration that was employed was SEM (structural equation modeling). The findings reveal that digital repurchase intention, e-service quality, and e-satisfaction are perceived by users as being at a high level. E-service quality indirectly influences online repurchase intention through e-satisfaction, highlighting the mediating role of customer satisfaction in driving repeat purchase behavior. Interestingly, the study also found that digital repurchase intention is not directly and significantly determined by the quality of e-services. These results underscore the importance of e-satisfaction as a bridge between digital purchasing intent and the quality of electronic services. Therefore, E-commerce platforms should focus on Addressing aspects of quality of service like responsiveness, reliability, and user-friendliness to foster customer satisfaction, which can lead to stronger repurchase intentions. The survey offers beneficial details to help e-commerce companies improve the way they operate. strategies to build customer loyalty and sustain competitive advantage.